DETERMINATION OF THE HEIGHT AND WIDTH OF THE COLLAPSE ZONE IN THE HORSESHOE TUNNEL BY NUMERICAL METHOD - Danava, Deo
The stability of underground openings or tunnels is a topic that is widely studied in the field of underground mining and civil infrastructure. For shallow tunnel, many still use empirically generated equations to determine the magnitude of the dead load of the collapse zone carried by the tunnel support. This study aims to analyze the effect of the dimension and depth of the tunnel on the height and width of the collapse zone using numerical models. The analysis is conducted by looking at the relationship between the spread of the plastic zone and the distribution of the vertical stress around the tunnel, especially at the roof of the tunnel to determine the height of the collapse zone and at the tunnel wall to determine the width of the collapse zone. The width of the tunnel model is varied from 5 m to 20 m, while the tunnel depth is varied from 10 m to 80 m. The results of this study indicate that the dimension and depth of the tunnel significantly influences the height and width of the collapse zone. Based on the result of plastic zone analysis, tunnel depth may now be classified into shallow, transitional and deep zones. The result is then compared with the existing dead load theories from Terzaghi and Protodyakonov.